2020
DOI: 10.30994/jqph.v3i2.78
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Psycological Disorder Tedency for Polygamous Women Reproductive Health in Pamekasan Madura

Abstract: The majority of polygamous marriages in Indonesia are only based on law and religion, regardless of the effects of polygamy. The lack attention public about the psychology that occurs in polygamous women. While, the impact of psychological disorders itself can affect to female hormones that can be caused to a reproduction system. The reproductive system can also experience disorders due to illness or abnormalities. The diseases of the reproductive system can be caused by germs, genetic factors, or hormones. Wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Moreover, I worry most about this marriage because the first wife knows. "From the informant's statement above, it can be concluded that the unregistered marriage he carried out made him depressed (Yunita., et. al., 2020;Mappigau, et.…”
Section: Women's Voices Regarding Sirri Marriage From a Psychological...mentioning
confidence: 99%
“…Moreover, I worry most about this marriage because the first wife knows. "From the informant's statement above, it can be concluded that the unregistered marriage he carried out made him depressed (Yunita., et. al., 2020;Mappigau, et.…”
Section: Women's Voices Regarding Sirri Marriage From a Psychological...mentioning
confidence: 99%